2009
DOI: 10.1007/s10646-009-0403-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cell-toxicity screening as an alternative animal model for coral toxicology: effects of heat stress, sulfide, rotenone, cyanide, and cuprous oxide on cell viability and mitochondrial function

Abstract: The logistics involved in obtaining and maintaining large numbers of corals hampers research on the toxicological effects of environmental contaminants for this ecologically and economically important taxon. A method for creating and culturing single-cell suspensions of viable coral cells was developed. Cell segregation/separation was based on specific cell densities and resulting cell cultures were viable for at least 2 mos. Low-density cells lacking symbiotic zooxanthallae and rich in mitochondria were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 67 publications
(91 reference statements)
0
40
1
Order By: Relevance
“…Enzyme digestion induces dissociation of individual cells and small cell clusters, which remain suspended or adhere to the culture substrate and may aggregate over time (Gates and Muscatine 1992;Frank et al 1994;Helman et al 2008;Downs et al 2010). The mesoglea gel separating the two epithelial layers (epiderm and gastroderm) of cnidaria is an extracellular matrix (ECM) which, in Hydra, has been reported to contain collagen type IV (Fowler et al 2000) associated to laminin in the subepithelial basal lamina and to fibrillar collagen type I (Shimizu et al 2008;Sarras 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzyme digestion induces dissociation of individual cells and small cell clusters, which remain suspended or adhere to the culture substrate and may aggregate over time (Gates and Muscatine 1992;Frank et al 1994;Helman et al 2008;Downs et al 2010). The mesoglea gel separating the two epithelial layers (epiderm and gastroderm) of cnidaria is an extracellular matrix (ECM) which, in Hydra, has been reported to contain collagen type IV (Fowler et al 2000) associated to laminin in the subepithelial basal lamina and to fibrillar collagen type I (Shimizu et al 2008;Sarras 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Alternately, coral soft tissue is chemically induced to detach, in response to removal of divalent cations (Gates and Muscatine 1992;Frank et al 1994;Kopecky and Ostrander 1999;Domart-Coulon et al 2001, 2004aMass et al 2012) or exposure to a reducing agent, such as N-acetylcysteine (Peng et al 2008). Enzymatic digestion has also been widely used to dissociate the tissue into single cells (Gates and Muscatine 1992;Frank et al 1994;Helman et al 2008;Downs et al 2010). Types and brand of enzymes used in dissociation studies vary between laboratories, and are often not detailed by authors, making it difficult to standardize protocols for coral cell isolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once tissue disaggregation occurred, the cell slurry was then subjected to two differential centrifugations using a swinging bucket rotor at 50 x g for 5 min. The cell slurry was then layered onto a Percoll ® step-gradient (as in Downs et al 2010;2013), and centrifuged at approximately 200 x g for 4 min (not shown). Different fractions of non-zooxanthella (term used for dinoflagellate symbiont, Symbiodinium sp.)…”
Section: Coral Cell Toxicity Assaymentioning
confidence: 99%
“…Calicoblasts were identified by having the highest intensity of red fluorescence; the largest number of mitochondria per cell (Davy et al 2012). Cells were cultured in a modified tissue culture media for 48 h (Downs et al 2010;2013). Coral cellculture media (pH 8.2) consisting of 1 mL RPMI-1640, 100x vitamin solution to 99 mL of SSS-ASW (36 ppt salinity), 50 mM Hepes/KOH (pH 8.2), 1 mM calcium chloride, 1 mM sodium pyruvate, 0.075 g/L D-glucose, 0.3 g/L galactose, 0.25 g/L sodium DL-lactate, 0.25 mM ascorbate, 0.05 g/L α-lipoic acid, 0.5 mM proline, 0.5 mM cysteine, 0.5 mM methionine, 0.01 mM hydroxycobalamin, 0.001 mM sodium folate, 1 g/L bovine albumin (V), 0.05 g/L succinate, and 0.25 g/L L-glutamine.…”
Section: Coral Cell Toxicity Assaymentioning
confidence: 99%